Peningkatan Kadar Protein Padi Melalui Mutagenesis Asam Amino Lisin Secara In Vitro - Nina Tanzerina; Juswardi Juswardi (Jurnal Penelitian Sains, 2003)
The research about metagenesis of lysine for increasing rice protein by in vitro had been conducted on July to November 2001, at Laboratory of Genetics and Biotechnology, Department of Biology, Faculty Mathematics and Natural Science, Sriwijaya University. The mutagenesis of lysine callus selected one step subculture with adding 2.0 mM of lysine on Murashige and Skoog medium. The total protein evaluated from the lysine mutant callus that growth and prolipheration on medium’s. The protein content measured with biuret reagent and bovine serum albumine as the standart protein. The result shown that no differences of colours, texture, and cell structure between lysine mutant and wild type (control) callus. The total protein increase to 71,53% on mutant lysine than wild type callus.